Usage of Information Technologies in Malaysian Businesses - Rosziati, Ibrahim; Jacey-Lynn, Minoi (JITI, 2005)
A survey on small and medium sized industries in Malaysia has been carried out in order to identify and recognize the usage of IT in business. The parameters such as organizational details (i.e. the numbers of employees, sales or profitability and the type of business) and managers details (in terms of educational level, computer literacy and computer experiences) were studied in order to see whether these parameters do contribute towards the usage of IT in business. Based on the survey, the results found are discussed and an IT adoption model is proposed.